2021
DOI: 10.1037/cpp0000369
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of parental self-efficacy on parental worry and social activity limitation associated with pediatric food allergy.

Abstract: Objective: Research has established associations between parental self-efficacy (SE) related to managing their child’s food allergy (FA) and parent quality of life, but there has been limited examination of how parent variables predict child social outcomes. This study examined whether parental SE related to managing their child’s FA moderates the association between parental worry and activity limitation of the child. Methods: Parents of 218 children with parent-reported FA completed an online survey, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In family relationships, parental support and conflicts with independence were common in adolescents with FA and despite most participants having a good relationship with their parents, some felt their parents wanted to ‘control their lives’ 25 . This is supported by recent research from McLaughlin, Humiston and Peterson 51 who found that as parental worry increased, so did limitations on children regarding FA‐related social activities. Previous research by Van der Velde et al 52 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In family relationships, parental support and conflicts with independence were common in adolescents with FA and despite most participants having a good relationship with their parents, some felt their parents wanted to ‘control their lives’ 25 . This is supported by recent research from McLaughlin, Humiston and Peterson 51 who found that as parental worry increased, so did limitations on children regarding FA‐related social activities. Previous research by Van der Velde et al 52 .…”
Section: Discussionmentioning
confidence: 89%
“… 53 highlighting the benefit of allergy clinics in supporting parents and McLaughlin et al. 51 suggesting that increasing parent self‐efficacy may help with reducing worry and social restriction of children with FA. Anxiety in adolescents with FA and parents 54 , 55 , as also shown by findings from this review, is a key area for clinicians, which may be supported by appropriate understanding of beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13,18,23,42 Caregivers experiencing high levels of anxiety about food allergy or low levels of self-efficacy around food allergy management may be more likely to limit the child's role in allergy management and participation in developmentally typical social, family, and school activities, with implications for the child's quality of life, anxiety level, and sense of empowerment. 22,41,[43][44][45] In contrast, "balanced" family coping with food allergy (eg, having sufficient levels of vigilance to sustain allergen avoidance and emergency preparedness, while being able to regulate anxiety and integrate food allergy management into daily life) has been associated with positive quality of life and child involvement in food allergy selfcare. 43 Such findings highlight the need for educational materials that support caregivers in educating children about food allergies and preparing them for self-care in ways that promote balanced coping with food allergy at all stages of child development.…”
Section: Developmental Aspects Of Managing and Coping With Food Allergymentioning
confidence: 99%